2018
DOI: 10.1016/j.cell.2018.03.072
|View full text |Cite|
|
Sign up to set email alerts
|

The Energetics and Physiological Impact of Cohesin Extrusion

Abstract: Cohesin extrusion is thought to play a central role in establishing the architecture of mammalian genomes. However, extrusion has not been visualized in vivo, and thus, its functional impact and energetics are unknown. Using ultra-deep Hi-C, we show that loop domains form by a process that requires cohesin ATPases. Once formed, however, loops and compartments are maintained for hours without energy input. Strikingly, without ATP, we observe the emergence of hundreds of CTCF-independent loops that link regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
468
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(538 citation statements)
references
References 57 publications
45
468
3
3
Order By: Relevance
“…Interestingly, the weakening of TAD boundaries was independent of CTCF binding (Fig E), suggesting supporting roles for transcription and CTCF in the formation of TADs and regulation of inter‐TAD interactions. This finding is consistent with previous reports that transcriptional inhibition as well as transcriptional elongation can displace cohesin from CTCF sites and disrupt chromatin interactions , correlating with weakening of TAD boundaries.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, the weakening of TAD boundaries was independent of CTCF binding (Fig E), suggesting supporting roles for transcription and CTCF in the formation of TADs and regulation of inter‐TAD interactions. This finding is consistent with previous reports that transcriptional inhibition as well as transcriptional elongation can displace cohesin from CTCF sites and disrupt chromatin interactions , correlating with weakening of TAD boundaries.…”
Section: Discussionsupporting
confidence: 93%
“…ª 2019 The Authors EMBO reports 20: e48068 | 2019 their fine-tuning (i.e., regulation of specific enhancer-promoter interactions or inter-TAD interactions) may be regulated by an interplay between loop extrusion and the act of transcription, in addition to the selective binding of transcription factors and chromatin modifiers at TAD boundaries [1,[55][56][57]. However, it is worth noting that Vian and colleagues have demonstrated that TADs can disappear upon cohesin degradation and reappear after rescue, even in the absence of transcription [32]. Similarly, previous reports suggested that the act of transcription can influence the 3D structure of the nucleus [27,[58][59][60].…”
Section: Proper Tad and Genomic Compartment Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of the insoluble debris, the lysate was incubated with specific antibodies against CTCF (07-729; Millipore), RAD21 (ab992; Abcam), or NIPBL (A301-779A; Bethyl Laboratories) and purified by protein A-agarose beads Millipore). NIPBL and CTCF ChIP-seq for the Igh locus were recently published [58]. ChIP DNA was extracted and prepared for high-throughput sequencing using a DNA library preparation kit for Illumina (NEB).…”
Section: Chip-seq Experimentsmentioning
confidence: 99%
“…Cohesin often establishes chromatin loops between enhancers and promoters [8]. Recent high resolution Hi-C studies have also found that cohesin makes contributions to interactions between enhancers and along gene bodies [78,79]. Substantial DNA helices can be opened during gene transcription, which would be potential targets for second DNA capture by cohesin (Figure 2(d)) [80].…”
Section: Intrachromosomal Interactions: Another Open Questionmentioning
confidence: 99%